Comparison of Carotid‐Femoral and Brachial‐Ankle Pulse‐Wave Velocity in Association With Target Organ Damage in the Community‐Dwelling Elderly Chinese: The Northern Shanghai Study. Issue 2 (February 2017) - Lu, Yuyan; Zhu, Mengyun; Bai, Bin; Chi, Chen; Yu, Shikai; Teliewubai, Jiadela; Xu, Henry; Wang, Kai; Xiong, Jing; Zhou, Yiwu; Ji, Hongwei; Fan, Ximin; et al.
Abstract : Background: Carotid‐femoral pulse‐wave velocity (cf‐PWV) and brachial‐ankle PWV (ba‐PWV) are the 2 most frequently applied PWV measurements. However, little is known about the comparison of hypertensive target organ damage (TOD) with cf‐PWV and ba‐PWV. Methods and Results: A total of 1599 community‐dwelling elderly subjects (age >65 years) in northern Shanghai were recruited from June 2014 to August 2015. Both cf‐PWV and ba‐PWV were measured using SphygmoCor and VP1000 systems, respectively. Within the framework of comprehensive cardiovascular examinations, risk factors were assessed, and asymptomatic TOD, including left ventricular mass index, peak transmitral pulsed Doppler velocity/early diastolic tissue Doppler velocity (E/Ea), carotid intima‐media thickness, arterial plaque, creatinine clearance rate, and urinary albumin‐creatinine ratio were all evaluated. Both PWVs were significantly associated with male sex, age, waist/hip circumference, fasting plasma glucose, and systolic blood pressure, and ba‐PWV was also significantly related to body mass index. Both PWVs were significantly correlated with most TOD. When cf‐PWV and ba‐PWV were both or separately put into the stepwise linear regression model together with cardiovascular risk factors and treatment, only cf‐PWV, but not ba‐PWV, was significantly associated with carotid intima‐media thickness and creatinine clearance rate ( P <0.05). When cf‐PWV and ba‐PWV were both or separately put into the same full‐mode model after adjustment for confounders, only cf‐PWV, but not ba‐PWV, showed significant association with carotid intima‐media thickness and creatinine clearance rate ( P <0.05). Similar results were observed in logistic regression analysis. Conclusions: Taken together, in the community‐dwelling elderly Chinese, cf‐PWV seems to be more closely associated with hypertensive TOD, especially vascular and renal TOD, as compared with ba‐PWV. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02368938.